TINGKAT PENETASAN RELATIF TELUR IKAN MAS (CYPRINUS CARPIO LINN) RAS PUNTEN YANG DIBERIKAN KEJUTAN SUHU PANAS UNTUK MEMPRODUKSI IKAN POLIPLOID - Muh. Khalifah Mustami (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
Cyprinus carpio Linn is kind of fresh water fish which is widely developed because it is liked by society. Therefore, an appropriate plantation system is needed in order the availability of the fish in aboundant. Plantation with steril fish is one of alternative of providing the fish apropriately. The research is aimed to know the relative hatching rate on Cyprinus carpio Linn ras Punten which is given heat shocking temperature after fertilization. The research design is used is Copletely Rendomized Design with four repeating for each experimental group. The data is analyzed using one way ANAVA to know the effect of heat shocking temperature treatment toward relative hatching rate. The result of the research show that there is a significant effect between treatment toward relative hatching rate with probability is 0,00.